Analysis of Tumour Size When Presented to Dental College: A Retrospective Institutional Study - Harsh Mohan Pathak1 , Satyabrata Pattnaik2 , Soumya Kanti Roy2 , Sanchari Sinha Roy2 , Kalyan Sundar (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objective: Evaluation of presentable tumor size in oral squamous cell carcinoma was the objective of thestudy.Patients and Method: The study sample comprised of ninety-eight biopsies diagnosed as oral squamouscell carcinoma presented to dental college from 2015 to 2020. Result and analysis of presentable tumor sizewhen reported.Results: Male to female ratio was 2.5:1. Among the 295 diagnosed OSCC cases presentable tumor sizeswhen reported, most of the cases were T2 (42.37%) followed by T1 (18.3%), T3 (11.86%), and T4 (6.1%).Conclusions: Oral squamous cell carcinoma is one of the major health problems in India. Strategies must bemade to improve the present scenario of health care service, where Government-run health care centres areburdened with ever-increasing patient pool, and to avail treatment in such centres is always a compromisewith time and health. Oral health and cancer awareness programs should be undertaken for prevention, earlydiagnosis, and management of the affected population. Regular long-term follow-up is also necessary forthese cases to avoid the recurrence of the disease and a better quality of life.